2022
DOI: 10.1177/20503121221138324
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fine Needle Aspiration Cytology and Histopathology in the diagnosis of lymph node pathologies at health facilities located in Hawassa: A 5-year retrospective study

Abstract: Objective: The aim of this study was to evaluate the performance of Fine Needle Aspiration Cytology in the diagnosis of lymph node pathologies in comparison with Histopathologic examination. Methods: A retrospective health facility-based cross-sectional study was carried out at health facilities located in Hawassa city among 101 patients who had both Fine Needle Aspiration Cytology and Histopathologic examination on the same site from 13 September 2016 to 30 August 2021. Background data were collected using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…On the other hand, we found FNAC to be more reliable at diagnosing metastatic malignancies, with an overall accuracy of 90.4%. This is supported by several authors who report an accuracy of FNAC of up to 95%-100% [15][16][19][20][21][22][23]. It has been suggested that since the diagnosis of metastatic carcinomas can be accomplished by relying only on cytomorphological features, unlike lymphoproliferative disorders, FNAC could be much more valuable in the diagnosis of metastatic malignancies than lymphomas.…”
Section: Discussionmentioning
confidence: 82%
“…On the other hand, we found FNAC to be more reliable at diagnosing metastatic malignancies, with an overall accuracy of 90.4%. This is supported by several authors who report an accuracy of FNAC of up to 95%-100% [15][16][19][20][21][22][23]. It has been suggested that since the diagnosis of metastatic carcinomas can be accomplished by relying only on cytomorphological features, unlike lymphoproliferative disorders, FNAC could be much more valuable in the diagnosis of metastatic malignancies than lymphomas.…”
Section: Discussionmentioning
confidence: 82%
“…The 1-year webinar covered the practical aspects of preparing samples from FNA for manual IHC in resource limited settings. The interactive webinar was attended by 98 participants from eight SSA countries, many of whom remarked on the high importance and relevance of the topic [ 17 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shariff et al report a sensitivity of 87.5%, specificity of 100%, and efficiency of 98% for FNAC (5). Taye et al reported that FNAC had an overall sensitivity of 88.2% and specificity of 92% for the diagnosis of lymphoma (18). Prasad and Mohan showed sensitivities, specificities, and positive and negative predictive values of 88.2%, 92%, 91.8%, and 88.5%, respectively (19).…”
Section: Discussionmentioning
confidence: 99%